Psychology of Advertising: Challenging Traditional Advertising Approaches (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Advertising, as currently practiced, ignores all thathas been learned by cognitive psychologists in the past 30 or 40 years.Consumers process all in coming information, including advertising, in a verycomplex yet instant Anew us manner. Advertising is not a stimulus in the outmodel behavioural psychology stimulus–response model of human informationprocessing. Advertising, if it is attended to at all, is nothing more than a netaddition to everything the consumer has previously learned and retained aboutthe brand. The challenge for advertising is to find ways and means to bypass orupset business as usual in the consumer’sbrainandtobuildanenduringperceptualrepresentationofthebrandasone that isacceptable and desirable.